1976
DOI: 10.1111/j.1399-3054.1976.tb03983.x
|View full text |Cite
|
Sign up to set email alerts
|

Variations in Zinc Content of Subcellular Fractions from Young and Old Roots, Stems and Leaves of Broad Beans (Vicia faba)

Abstract: 65Zn labelled seeds of broad beans (Vicia faba L.) germinated and grown in a complete nutrient solution containing the radioisotope were used to investigate the change in the subcellular distribution of this trace element during subsequent development of the labelled seeds. Homogenates of leaves, stems and roots were fractionated into cell‐wall debris, nuclei, chloroplasts, mitochondria, ribosomes and “soluble” fraction. The concentration of the radioisotope in these fractions, expressed as cpm/mg dry weight, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

1978
1978
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…The accumulation of zinc does not, however, simply follow the overall increase in organ weight, since there is a certain decrease with age of the zinc concentrations in the leaves (Table 2). Polar (1976) Figure 5. Growth of the'total "'Zn conten fthe individ Figure 6 Retatinn/hir, between the fresh <^aWosed Xi'^*;;^^^^^^^ê quilibrium).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The accumulation of zinc does not, however, simply follow the overall increase in organ weight, since there is a certain decrease with age of the zinc concentrations in the leaves (Table 2). Polar (1976) Figure 5. Growth of the'total "'Zn conten fthe individ Figure 6 Retatinn/hir, between the fresh <^aWosed Xi'^*;;^^^^^^^ê quilibrium).…”
Section: Discussionmentioning
confidence: 99%
“…Figure 6 Retatinn/hir, between the fresh weight of the first and second leaves, and their total ^Zn content tn Itght (open symbols) and d i h l d 10 h 6 l h leaves of Viciafaba, The zinc concentration in the different tissue is proposed to be correlated with the number of binding sites. Numerous organic compounds may act as binding sites for zinc e,g, DNA polymerases (Vallee 1977), RNA polymerases (Falchuk et al, 1976), ribosomal RNA (Wacker 1962, Prask and Plocke 1971, Polar 1976) and carbonic anhydrase (Randall and Bouma 1973). The age dependence of the concentration of some of these "binding sites", i.e, rRNA of chloroplasts and cytoplasm of spinach plants, was studied by Detchon and Possingham (1972).…”
Section: Discussionmentioning
confidence: 99%
“…Hewitt (1963) stated that, in many plant species, Zn deficiency results in agglutination of plastids, which then vacuolate and fill with tannin-lipid complexes or undergo lysis such that cell membranes lose their semipermeable properties. Polar (1976) speculated that a certain threshold leve1 of Zn is necessary for a11 subcellular plant organelles, where it plays a primarily structural role in organelle membranes. Safaya (1976) suggested that Zn has the ability to control the rate of P absorption by root cells through some functional association in the cell membrane.…”
mentioning
confidence: 99%
“…Chemical characterization of the low molecular weight components resulted in the identification of nine amino acids which were identical in roots and leaves. Cd in bean plants is assumed to be bound to peptides and/or proteins of low molecular weight.Cd is a major environmental contaminant (8,22). The essentiality of this element for either plants or animals has not yet been demonstrated, whereas its toxicity in higher concentrations is well established (8, 16).…”
mentioning
confidence: 99%
“…Cd is a major environmental contaminant (8,22). The essentiality of this element for either plants or animals has not yet been demonstrated, whereas its toxicity in higher concentrations is well established (8,16).…”
mentioning
confidence: 99%